Study of the Relationship between the Rotation of External Auditors and Audit Quality - LETAIFA, Wissal BEN; SBICA, Malek (Journal of Ecohumanism, 2024)
Purpose - The objective of this research is to study the relationship between external auditor turnover and audit quality. To do this, we chose two measures of audit quality, namely discretionary accruals and the auditor's opinion. Design/methodology/approach - Using a sample of 37 Tunisian companies listed during the period from 2015 to 2021, the paper uses a logistic regression to investigate the association between the quality of the audit and the rotation of the auditors. Findings - The results obtained based on linear and logistic regression invalidate the two hypotheses which assume on the one hand that a long-term mandate negatively influences the quality of the audit, on the other hand the assumption that the rotation of the auditors has a positive impact on the quality of the audit. Contrary to what was expected in our research, the results of the logistic regression show that a long-term audit mandate has a positive effect on audit quality. Research limitations/implications – This research may be of interest to many developing countries that has not a lot of studies on the audit turnover. Future research should focus on the link between audit turnover consequences to overcome the gap which might exist in the literature. Practical implications – Previous studies has shown how it is important to focus on audit opinion to reduce asymmetric information between managers and stockholders. And, this study offers some insights about audit shipping that should be analyzed to understand audit turnover. Originality/value – This research highlights the role of audit opinion in the rotation of auditors in emerging markets. Consideration of this relationship may contribute to the understanding of the auditor turnover in developing countries.